One-pot, selective synthesis of orthorhombic and rhombohedral NaNbO3 by hydrothermal method - Van, Nguyen Duc (Vietnam Journal of Chemistry, 2017)
The pure orthorhombic- and rhombohedral-structure NaNbO3 microcrystals were obtained selectively by a facile, additive-free hydrothermal procedure using commercialized Nb2O5, NaOH, KOH as starting materials. The obtained samples were characterized by X-ray powder diffraction, field-emission scanning electron microscopy, energy dispersive spectrometry, Raman spectroscopy. The results showed that the required hydrothermal temperatures to synthesize single crystalline phase of rhombohedral and orthorhombic NaNbO3 are as low as 180 and 200 oC for 24 h, respectively. The phase composition of the hydrothermal product was found to be strongly dependent on (K+ + Na+)/Nb5+ molar ratio. Interestingly, by using the (K+ + Na+)/Nb5+ molar ratio of 9.0, the pure metastable phase of NaNbO3 with rhombohedral structure was readily synthesized in the hydrothermal temperature range of 180-200 oC. However, as this molar ratio crossed over 12.0, the polymorphic type of NaNbO3 was received at 180 oC only and the orthorhombic type existed purely when the reaction temperature reached 200 oC. Keywords. NaNbO3, surfactant-free, polymorphism, hydrothermal method.